2021
DOI: 10.1016/j.omto.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

miR-301 regulates the SIRT1/SOX2 pathway via CPEB1 in the breast cancer progression

Abstract: Breast cancer, the most common malignant tumor in women, has become a worldwide burden for family and society. MicroRNAs (miRNAs or miRs) are recognized as critical mediators of cancer-related processes, since they have the ability to coordinately suppress multiple target genes. In this study, we aim to find out specific miRNAs involved in the progression of breast cancer and explore the underlying molecular mechanism. Bioinformatics analysis suggested miR-301 as a differentially overexpressed miRNA in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…By inhibiting p53 [43] or promoting the activity of PI3K/Akt signaling pathway [44], SIRT1 enhanced proliferation of BC cells. In nude mice models, miR-301 overexpression accelerates the progression of BC by mediating the SIRT1/SOX2 pathway [45]. Additionally, SIRT1 plays a pivotal role in the regulation of the epithelial-mesenchymal transition (EMT) process, which contributes to the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting p53 [43] or promoting the activity of PI3K/Akt signaling pathway [44], SIRT1 enhanced proliferation of BC cells. In nude mice models, miR-301 overexpression accelerates the progression of BC by mediating the SIRT1/SOX2 pathway [45]. Additionally, SIRT1 plays a pivotal role in the regulation of the epithelial-mesenchymal transition (EMT) process, which contributes to the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,21,35,36 Its inhibitory effect against apoptosis has been reported in a range of cancers, including breast cancer, ovarian cancer, and prostate cancer. 22,31,37 miRNAs are believed to exert their functional effects by targeting genes using distinctive signalling pathways that have already been implicated in cancers. We previously reported on COM involvement for different KEGG pathways, including the JAK-STAT, NF-kB, MAPK, PI3K-AKT, and AMPK signalling pathways, based on miRNA or transcriptomic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Among these miRNAs, miR‐301a is upregulated in many cancers and is reportedly responsible for promoting cell migration and proliferation and inhibiting apoptosis 14–24 . Indeed, we previously identified miR‐301a as one of the aberrantly expressed miRNAs in COM, when tissues were screened using next‐generation sequencing 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that the HDAC SIRT1 is upregulated in NEPC and showed that overexpressing SIRT1 promotes NEPC lineage plasticity ( 94 ). SIRT1 has been shown to promote upregulation of SOX2 in breast cancer ( 97 ), liver cancer stem cells ( 98 ), and bone marrow-derived mesenchymal stem cells ( 99 ). Thus, it is possible that SOX2 upregulation by SIRT1 may also contribute to NEPC lineage plasticity.…”
Section: The Role Of Epigenetic Change In Nepc Lineage Plasticitymentioning
confidence: 99%